1995
DOI: 10.1093/rheumatology/34.7.647
|View full text |Cite
|
Sign up to set email alerts
|

A 5-Year Follow-Up of a Controlled Trial of an Arthritis Education Programme

Abstract: A 5-yr follow-up of an arthritis education programme is reported. After adjustment for those lost, deceased or moved away, the 5-yr response rate was 75% among intervention subjects and 78% among controls. Individuals who participated in the education programme maintained their increased knowledge in some aspects. The relative difference in pain and disability over 5 yr was greater in the control group. Most individuals were less active at practising exercise after 5 yr. Improvement in performing exercise and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
5

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 0 publications
1
37
0
5
Order By: Relevance
“…Little is known about benefits beyond 12 months as only two had longer-term follow-ups, although both showed some continuing benefits 14 23. Previous research has identified that the ASMP led to sustained benefits over 4 years and was cost-effective46—a multidisciplinary 20 h programme over 8 weeks led to significantly less pain in comparison with the control group at 5 years,47 and a 10 h educational-behavioural programme over 4 weeks led to significantly better function in comparison with the control group at 4 years48—but more research is needed in other SMIs. We recommend that SMI studies that demonstrate benefits at 6–12 months should seek funding to extend follow-up and evaluate cost-effectiveness, to provide data for service development decisions.…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…Little is known about benefits beyond 12 months as only two had longer-term follow-ups, although both showed some continuing benefits 14 23. Previous research has identified that the ASMP led to sustained benefits over 4 years and was cost-effective46—a multidisciplinary 20 h programme over 8 weeks led to significantly less pain in comparison with the control group at 5 years,47 and a 10 h educational-behavioural programme over 4 weeks led to significantly better function in comparison with the control group at 4 years48—but more research is needed in other SMIs. We recommend that SMI studies that demonstrate benefits at 6–12 months should seek funding to extend follow-up and evaluate cost-effectiveness, to provide data for service development decisions.…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…Adherence to prescription of physical exercise was considered in these studies 18-21. Only Lindroth et al found effects on compliance with ergonomic measures 21. These studies did not take medication into account.…”
mentioning
confidence: 99%
“…Type of arthritis was recorded by the case manager. A composite physical factor (from -1 to +1) was created through a factor score resulting from factor analysis of various scales that evaluated pain intensity, fatigue,(0–100 VAS)[13] limitations and stiffness (0–5 WOMAC)[31]. Those scales were used in various study on with arthritis individuals [6,32-34].…”
Section: Methodsmentioning
confidence: 99%
“…Barlow et al [14] observed that individuals with arthritis who participated in a community-based self-management intervention successfully maintained changes in communication with physician, use of strategies of distraction and visualization, performance of relaxation and flexibility exercises at 4 and 12 months post-intervention. Conversely, Lindroth et al [12] found that among rheumatoid arthritis (RA) participants, frequency of practice was not maintained either at 12 months post-intervention or 5 years later [13]. Finally, the only study evaluating maintenance of changes from a home-based arthritis intervention showed that improvements in frequency of walking and level of household and self-care activities were maintained [16] for RA participants at 12 and 52 weeks post-intervention.…”
Section: Introductionmentioning
confidence: 99%